2007
DOI: 10.2136/sssaj2006.0229
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and Cover Cropping Effects on Aggregate‐Protected Carbon in Cotton and Tomato

Abstract: T he soil C sequestration potential of reduced tillage or CT has been extensively studied in other parts of the country, but there has been very little CT research under arid, irrigated agriculture systems, like those in California. California cropping systems are intensively managed and require tillage operations to address furrow irrigation needs. Diverse crop rotations and crops untested for reduced tillage regimes have complicated the development of CT approaches in this highly productive agricultural regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…There are studies which showed the necessity of long term experiments to obtain benefits in the TOC contents. However, in our study higher TOC were found in the CC treatments since 2012 that are in agreement with other short term experiments (Nivelle et al, 2016;Veenstra et al, 2007). Particularly, Villamil et al (2006) and Mazzoncini et al…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…There are studies which showed the necessity of long term experiments to obtain benefits in the TOC contents. However, in our study higher TOC were found in the CC treatments since 2012 that are in agreement with other short term experiments (Nivelle et al, 2016;Veenstra et al, 2007). Particularly, Villamil et al (2006) and Mazzoncini et al…”
Section: Resultssupporting
confidence: 93%
“…From 2008 until 2016, there were increases of 39% after barley, 36% after vetch and 25% after fallow. Some studies showed that the combination of no tillage and use of CC is necessary to increase the TOC content (Nivelle et al, 2016;Veenstra et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of cover crops can bring increases in soil organic matter and related benefits under both types of management (Lal et al 1998b;Veenstra et al 2007), and can be an important part of long-term and short-term fertility programs. In developing a management approach for reduced tillage alternatives, it is important to understand the N supplied by as well as any interactions between fertilizer and cover crops.…”
Section: Introductionmentioning
confidence: 99%